Intellectual Capital Food And Beverage Sub-Sector Manufacturing Companies And The Factors - Dirvi Surya Abbas; Arry Eksandy (International Journal of Science, Technology & Management, 2021)
The Purpose of this study was to determine the effect of company age, leverage, and independent commissioners on intellectual capital in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (BEI). The research time period used is 3 years, namely the 2016-2018 period. The population of this study includes all food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2016-2018 period. The sampling technique was using purposive sampling technique. Based on the predetermined criteria, 17 companies were obtained. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analysis method used is panel data regression analysis. The results showed that Leverage and Independent Commissioner had no influence on Intellectual Capital. However, the variable company age has an influence on intellectual capital.